A network-based global mobility management architecture. (4th December 2009) - Zhou, Huachun; Luo, Hongbin; Zhang, Hongke; Lo, Chi-Hsiang; , Han-Chieh Chao
This paper specifies a network-based global mobility management architecture, named NetGMM. NetGMM supports network-based mobility management and non-Mobile IP mobile environment. There are two design considerations. The first is that a future mobile network requires network-based mobility management, shifting the mobility management function from Mobile Nodes (MN) to Access Network (AN) nodes. The second is that future mobile networks will support IP multi-services, introducing a separation between network address and identity of a mobile node entity, allowing heterogeneous networks to work together without loss of functionality.